Supraharmonics in Power Grid: Identification, Standards, and Measurement Techniques - Alfalahi S.T.Y.; Alkahtani A.A.; Al-Shetwi A.Q.; Al-Ogaili A.S.; Abbood A.A.; Mansor M.B.; Fazea Y. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric power system control; Power electronics; Power quality; Renewable energy resources; Smart power grids; Switching frequency; Electric power; Electric power distribution systems; Electrical distribution system; Frequency ranges; Measurement techniques; Measuring technique; Power electronics devices; Renewable energy systems (RES); Electric power transmission networks